Profit-shifting behaviour of emerging multinationals from India - Khanindra Ch. Das (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper examines the profit-shifting behaviour of emerging multinational firms from India. It is found that the before-tax profitability of subsidiaries differs according to whether they were established directly or via an Offshore Financial Centre (OFC). The impact of the corporate tax rate on profitability is examined using a fixed-effects model for the period 2010-19. In the case of subsidiaries established via OFCs, a negative relationship between corporate tax rate and profitability is found, indicating profit-shifting behaviour. However, a disaggregated investigation by characteristics of parent firms reveals that the negative relationship holds primarily for via-OFC subsidiaries that belong to multinational firms with limited transactions of intangible assets, lower export intensity, and limited dependence on external commercial borrowing. The evidence of profit shifting is not all pervasive. However, in the presence of these transaction channels, multinational firms establish better control over intra-firm resources, which enables the transfer of resources within the multinational firm when the network of subsidiaries is connected through the OFC. The results are robust to the inclusion of economic and institutional factors pertaining to the host country.
Keywords: F23; H26; 330; corporate tax; multinational firms; offshore financial centre; profit shifting; panel data; tax haven